What is the best time point to identify patients at risk of developing persistent low back pain? - Melloh, Markus; Elfering, A.; Käser, A.; Rolli Salathé, C.; Crawford, R.; Barz, T.; Zweig, T.; Aghayev, E.; Röder, C.; Theis, J. (IOS Press, 2015)
BACKGROUND: Early identification of patients at risk of developing persistent low back pain (LBP) is crucial. OBJECTIVE: Aim of this study was to identify in patients with a new episode of LBP the time point at which those at risk of developing persistent LBP can be best identified. METHODS: Prospective cohort study of 315 patients presenting to a health practitioner with a first episode of acute LBP. Primary outcome measure was functional limitation. Patients were assessed at baseline, three, six, twelve weeks and six months looking at factors of maladaptive cognition as potential predictors. Multivariate logistic regression analysis was performed for all time points. RESULTS: The best time point to predict the development of persistent LBP at six months was the twelve-week follow-up (sensitivity 78%; overall predictive value 90%). Cognitions assessed at first visit to a health practitioner were not predictive. CONCLUSIONS: Maladaptive cognitions at twelve weeks appear to be suitable predictors for a transition from acute to persistent LBP. Already three weeks after patients present to a health practitioner with acute LBP cognitions might influence the development of persistent LBP. Therefore, cognitive-behavioral interventions should be considered as early adjuvant LBP treatment in patients at risk of developing persistent LBP.